2010
DOI: 10.1038/modpathol.2010.86
|View full text |Cite
|
Sign up to set email alerts
|

BRAF mutation influences hypoxia-inducible factor-1α expression levels in papillary thyroid cancer

Abstract: Hypoxia-inducible factor-1a is found frequently overexpressed in solid tumors cells, exerting an important role in angiogenesis, glucose metabolism, cell proliferation, survival and invasion. In thyroid carcinomas, hypoxiainducible factor-1a expression was found increased in differentiated, poorly differentiated, medullary and anaplastic variants. Hypoxia represents the principal stimulus responsible for hypoxia-inducible factor-1a induction. Other nonhypoxic stimuli increase hypoxia-inducible factor-1a synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 31 publications
2
40
0
2
Order By: Relevance
“…Rather than GLUT-1, 18 F-FDG uptake of PTC may be associated with HIF-1α [3] or GLUT-3 or −4 [1]. Zerilli et al [24] suggested that the BRAF mutation-mediated signaling pathway may regulate the expression of HIF-1α. Further studies are needed to clarify the relationship of 18 F-FDG uptake, the expression of variable glucose transporters, HIF-1α, and the BRAF mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than GLUT-1, 18 F-FDG uptake of PTC may be associated with HIF-1α [3] or GLUT-3 or −4 [1]. Zerilli et al [24] suggested that the BRAF mutation-mediated signaling pathway may regulate the expression of HIF-1α. Further studies are needed to clarify the relationship of 18 F-FDG uptake, the expression of variable glucose transporters, HIF-1α, and the BRAF mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Following the activation of the MAPK pathway, secondary molecular events occur, such as hypomethylation and genome-wide hypermethylation, which augment the tumorigenic activity of this pathway [52]. In addition, upregulation of several oncogenic proteins, such as chemokines [53,54], nuclear factor B (NF-B) [55], vascular endothelial growth factor A (VEGFA) [56], matrix metalloproteinases (MMPs) [53,55,57], MET [58,59], vimentin [60], prokineticin 1 (PROK1; also known as EG VEGF) [61], prohibitin [62], hypoxia-inducible factor 1␣ (HIF1␣) [63], thrombospondin 1 (TSP1) [64], urokinase plasminogen activator (uPA) and its receptor (uPAR) [65,66] and transforming growth factor ␤1 (TGF␤1) [67,68] drive cancer cell growth, proliferation and survival, together with tumor angiogenesis, invasion and metastasis.…”
Section: The Mapk Signaling Pathwaymentioning
confidence: 99%
“…HIF1 induces expression of VEGF, a growth factor, and MET, an oncogene, which are also upregulated in thyroid tumors as compared to normal thyroid tissues [162]. On the other hand, PI3K-AKT and MAPK increase expression of HIF1 in thyroid tumor [161,164,165] while a mutation in BRAF (V600E) also affects expression levels of HIF1␣ in papillary thyroid cancer [165]. Interestingly, inhibition of expression levels of HIF-1␣ and HIF-2␣ by GDC-0941 in four different thyroid tumor cells (BcPAP, WRO, FTC133, and 8505c) resulted in inhibition of VEGF secretion [166].…”
Section: The Hif1α Pathwaymentioning
confidence: 99%
“…The BRAF V600E mutation, which causes the constitutive activation of a serine/threonine kinase, was shown to be an initiating event for the disease and also to promote proliferation, tumorigenicity, and dedifferentiation processes through the activation of the MAPK pathway (Knauf et al 2005, Liu et al 2007. Moreover, BRAF V600E mutation seems to increase the expression of vascular endothelial growth factor (VEGF) and hypoxia-inducible factor-1 alpha (HIF1α), and thus, targeting the product of the BRAF V600E mutation may have the dual effects of blocking the tumor's progression and reducing tumor angiogenesis (Jo et al 2006, Zerilli et al 2010. Although still controversial, there is a general agreement that the BRAF V600E mutation is associated with more aggressive clinical-pathological features, loss of 131 I avidity, and increased recurrence and mortality rates (Nikiforova et al 2003, Elisei et al 2008, Riesco-Eizaguirre et al 2006.…”
Section: Molecular Alterations In Thyroid Cancer and The Rationale Fomentioning
confidence: 99%
“…Angiogenesis is promoted by VEGF, which is overexpressed in response to intratumoral hypoxia via the overactivation of HIF1α. This transcriptional factor is upregulated not only by hypoxia but also via growth factor signaling pathways, such as PI3K/AKT and MAPK, and is expressed in thyroid cancer cells, especially in ATC cells, but not in normal thyroid tissue (Burrows et al 2010, Zerilli et al 2010). An important target of HIF1α is the MET oncogene that is upregulated in many thyroid cancers and promotes angiogenesis as well as cellular motility, invasion, and metastasis (Rong et al 1994, Ramirez et al 2000, Scarpino et al 2004.…”
Section: :4mentioning
confidence: 99%